Examining the Levels of Depression among University Students during the Final Assignment - Nurhalijah Munthe; Muhammad Putra Dinata Saragi (Journal of Educational, Health and Community Psychology, 2023)
Depression is a psychological condition characterized by a persistent feeling of sadness, hopelessness, emptiness, and despair, which affects an individual's emotional state, thoughts, and behavior. This research aims to determine the extent of depression experienced by students during the post-pandemic while completing their final assignments. The study utilizes a Mixed Method Research (MMR) approach with a Sequential Explanatory design that combines qualitative and quantitative methods. The research participants consist of 200 students from the 2019 class at the State Islamic University of North Sumatra. The research was conducted from February 1-20, 2023, and followed up with interviews from February 21-23, 2023. The results reveal that male students experience a higher level of depression than female students. The faculty with the highest number of depressed students is the Faculty of Da'wah and Communication, with 76 students (38%), although the statistical significance is not established. The majority of the students (31.5%) experience moderate depression. The research identifies various factors that contribute to depression, including parental expectations, difficulty in understanding the research materials, lack of references, difficulty in meeting with lecturers, repeating research, financial constraints, loss, and laziness among students.